True sea stories - Brook, Henry (Usborne London, 2005)
This book recounts stories of courage, heroism and disaster on the high seas. It covers famous as well as lesser-known stories, from Francis Drake's voyage on the Golden Hinde to the terror of the Piper Alpha disaster